Of bicycles, bakelites, and bulbs: toward a theory of sociotechnical change - Bijker, Wiebe E. (Cambridge, 1997)
"Of Bicycles, Bakelites and Bulbs This text attempts to found a full-scale theory of sociotechnical change that describes where technologies come from and how societies deal with them, using the examples of the safety bicycle, the first truly synthetic plastic, and the fluorescent light bulb."